The potency of actinomycetes extracts isolated from Pramuka Island, Jakarta, Indonesia as antimicrobial agents - Setiawati Setiawati; Titik Nuryastuti; Eti Nurwening Sholikhah; Puspita Lisdiyanti; Sylvia Utami Tunjung Pratiwi; TRI RATNA SULISTIYANI; SHANTI RATNAKOMALA; Jumina Jumina; Mustofa Mustofa (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Setiawati S, Nuryastuti T, Sholikhak EN, Lisdiyanti P, Pratiwi SUT, Sulistiyanti TR, Ratnakomala S, Jumina, Mustofa. 2021. The potency of actinomycetes extracts isolated from Pramuka Island, Jakarta, Indonesia as antimicrobial agents. Biodiversitas 22: 1104-1111. Actinomycetes are one of the Gram-positive bacteria which are widely distributed and produce many secondary metabolites including those known as antibiotics, antifungals, anticancer, and antimalarials agents. The secondary metabolites of actinomycetes are abundant, which include many active compounds that have been identified because of the large diversity in the actinomycetes phylum. This study aimed to identify and screen collected by Indonesian Culture Collection (InaCC) from Bojong Gede and Pramuka Island, Jakarta, Indonesia as antibacterial and antifungal agents. Primary screening was done on 16 actinomycetes isolates by well-agar diffusion method. Antimicrobial activity was tested by using micro broth dilution methods to determine minimum inhibitory concentration (MIC). Molecular identification into level genera and species was determined by 16S rRNA gene sequencing. Out of 16 actinomycetes isolates used, 4 isolates have activity against Candida albicans ATCC 10231, Staphylococcus aureus ATCC 6538, Bacillus subtilis BTCC B-612, and Escherichia coli BTCC B-614, specifically InaCC A758, InaCC A759, InaCC A760 and InaCC A765 isolates. InaCC A758 have highest antimicrobial activity against mentioned microbial with MIC value at 50 ?g/mL, 6.25 ?g/mL, 31.25 ?g/mL and 3.125 ?g/mL, respectively. Three genera were found from the samples: i.e. Streptomyces (80%), Microbispora (13%) and Nocardia (6%). Based on 16S rRNA gene identification, the active isolates of actinomycetes InaCC A758, InaCC A759, InaCC A760 and InaCC A765 were similar to Streptomyces badius, Streptomyces olivaceus, Streptomyces sanyensis, and Nocardia otitidiscaviarum, respectively. The secondary metabolites of actinomycetes extracts from Pramuka Island can be potentially developed as antifungal and antibacterial agents.